2017
DOI: 10.3389/fimmu.2017.00435
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor in Bone Marrow-Derived Cells Aggravates Tuberculosis Caused by Hypervirulent Mycobacterium bovis

Abstract: Tuberculosis (TB) remains a serious public health problem despite the great scientific advances in the recent decades. We have previously shown that aggressive forms of TB caused by hypervirulent strains of Mycobacterium tuberculosis and Mycobacterium bovis are attenuated in mice lacking the P2X7 receptor, an ion channel activated by extracellular ATP. Therefore, P2X7 receptor is a potential target for therapeutic intervention. In vitro, hypervirulent mycobacteria cause macrophage death by a P2X7-dependent mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…So, the deleterious effects of P2X7 receptor observed in hypervirulent mycobacteria infection may be related to a vicious cycle where high eATP amounts are released by damaged cells, exacerbating inflammation, lung damage, and bacillus spreading (Amaral et al, 2014 ). Bomfim et al ( 2017 ) recently showed that bone marrow-derived cells expressing P2X7 receptor have a critical role in promoting progression of severe tuberculosis. Therefore, P2X7 receptor is a key player in the modulation of immune responses against mycobacterium infections presenting protective or deleterious effects depending on mycobacterial strains.…”
Section: P2x7 Receptor In Infectious Diseases—angel or Demon Dependinmentioning
confidence: 99%
“…So, the deleterious effects of P2X7 receptor observed in hypervirulent mycobacteria infection may be related to a vicious cycle where high eATP amounts are released by damaged cells, exacerbating inflammation, lung damage, and bacillus spreading (Amaral et al, 2014 ). Bomfim et al ( 2017 ) recently showed that bone marrow-derived cells expressing P2X7 receptor have a critical role in promoting progression of severe tuberculosis. Therefore, P2X7 receptor is a key player in the modulation of immune responses against mycobacterium infections presenting protective or deleterious effects depending on mycobacterial strains.…”
Section: P2x7 Receptor In Infectious Diseases—angel or Demon Dependinmentioning
confidence: 99%
“…In severe pulmonary infection-induced ALI models, P2X 7 R is involved in the exacerbated inflammatory injuries and neutrophil infiltration. Severe tuberculosis and pulmonary injury are caused when mice are infected with hypervirulent Mycobacterium bovis ( 71 ). Chimeric mice that lack P2X 7 R in BM-derived cells show alleviated pulmonary injury, which demonstrates that P2X 7 R in BM-derived cells plays a critical role in the progression of severe tuberculosis.…”
Section: Purinergic Signaling Shapes Neutrophil Immunity In Pathologimentioning
confidence: 99%
“…By contrast, a study demonstrated that mice lacking P2X7R had a higher mycobacterial burden in the lungs compared to WT animals infected intravenously with a high dose of the common laboratory strain H37Rv (Santos et al, 2013 ). However, two recent papers suggested a role for the P2X7R in Bone Marrow-derived cells in aggressive forms of tuberculosis only (Amaral et al, 2014 ; Bomfim et al, 2017 ). In these studies, mice deficient for the P2X7R infected with virulent strains (Beijing1471 or MP287/03), but not with H37Rv strain, were less susceptible than WT mice (Amaral et al, 2014 ).…”
Section: Eatp and P2x7 Receptor: The Killer Side Of The Forcementioning
confidence: 99%
“…In these studies, mice deficient for the P2X7R infected with virulent strains (Beijing1471 or MP287/03), but not with H37Rv strain, were less susceptible than WT mice (Amaral et al, 2014 ). Infected P2X7R KO mice or chimeric mice adoptively transferred with P2X7R KO bone marrow cells presented a decrease in the bacterial load and in the gross pathology in the lungs compared to their counterparts (Amaral et al, 2014 ; Bomfim et al, 2017 ). Moreover, the authors showed that hypervirulent mycobacteria induce macrophage necrosis in a P2X7R-dependent mechanism (Amaral et al, 2014 ).…”
Section: Eatp and P2x7 Receptor: The Killer Side Of The Forcementioning
confidence: 99%